Blockchain Technology Improves Supply Chain Finance For Effective Supply Chain Management - Lihong, Yang; Selamat, Mohamad Hisyam (International Journal of Psychosocial Rehabilitation, 2020)
Under competitive global environment increasing pressures like short-term financing needs push companies trying hard to release potential fund within supply chains. The next frontier to improve productivity is then connected to the new concept of supply chain finance. Better visibility, authenticity, immutability, transparency and other features originated from blockchain technology have a special meaning to the complex transaction patterns of the supply chain. Together with smart contract, blockchain technology will improve the quality of supply chain finance by resolving issues like disadvantages of trust, enabling greater efficiency in financing activities, and avoiding fraudulency. This paper's intention is to produce a conceptual framework of effective supply chain management with blockchain-facilitated supply chain finance. How to establish a new ecosystem will be explored to find an optimal situation for buyers, suppliers and financiers to improve liquidity, product offering, and capital allocation throughout the value chain. As the Industrial 4.0 is bringing so many changes we believe the blockchain-driven supply chain will get more prosperous in global business.